A Review on Mechanical Automation Control System - Ji, Hongjie; Ji, Hongbo (Journal of Theory and Practice of Engineering Science, 2024)
With the continuous improvement of our country's economic strength, the level of industrial technology is also continuous progress, our country began the development of mechanical automation. In this paper, the mechanical automation control system is summarized, to understand its definition and working principle, the characteristics of mechanization automatic technology analysis, clear mechanical automation control system development points.